2008
DOI: 10.1614/ws-07-163.1
|View full text |Cite
|
Sign up to set email alerts
|

Factors Affecting Germination of Coolatai Grass (Hyparrhenia hirta)

Abstract: Coolatai grass is an invasive, perennial grass from Africa and the Middle East that has infested large areas of northern New South Wales, Australia, and also occurs in other Australian states. An understanding of the seed germination ecology of Coolatai grass can assist in predicting its potential distribution and developing effective management strategies. The effects of various environmental factors on Coolatai grass seed germination were investigated in a series of laboratory experiments. The effect of diur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 22 publications
(26 reference statements)
2
18
0
Order By: Relevance
“…Germination of coolatai grass was 92% at pH level of 7.00, however at moderate level of pH (5.00) or (9.00) germination was reduced by around 10%. Germination of coolatai grass was reduced at pH level of 4.00 or 10.00 (Chejara et al, 2008). Similar results to those of Chauhan et al (2006f) were found in Lolium rigidum (rigid ryegrass).…”
Section: Effect Of Phsupporting
confidence: 89%
See 1 more Smart Citation
“…Germination of coolatai grass was 92% at pH level of 7.00, however at moderate level of pH (5.00) or (9.00) germination was reduced by around 10%. Germination of coolatai grass was reduced at pH level of 4.00 or 10.00 (Chejara et al, 2008). Similar results to those of Chauhan et al (2006f) were found in Lolium rigidum (rigid ryegrass).…”
Section: Effect Of Phsupporting
confidence: 89%
“…Soil pH is another important environmental factor affecting seed germination of various weeds. Seeds of some weeds can germinate over a broad pH range (Chachalis et al, 2008;Chejara et al, 2008), while other weeds can germinate well in acidic soil conditions (Fried et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Germination is the process whereby seeds begin to sprout and grow. This process is affected by such factors as temperature (Widderick et al, 2004), drought (Chejara et al, 2008), salts (Chauhan et al, 2006) and burial depth (Koger et al, 2004). The present paper is concerned with the germination of catchfly (Silene conoidea) seeds.…”
Section: Introductionmentioning
confidence: 99%
“…Other ecological novelties have also been identified retrospectively among the high-impact species. These include an ability to perform well under high-light conditions (Robbins 2009), rapid post-rain germination (Keir and Vogler 2006;Vogler and Owen 2008), broad germination requirements that include the ability to germinate in drier soils than native species (Chejara et al 2008) and the ability to rapidly exploit phosphorus through fast-growing root systems (Christie 1975;Christie and Moorby 1975). However, the potential of such ecological novelties to enable species to successfully invade and become dominant without the assistance of anthropogenic disturbance still needs to be properly tested.…”
Section: Ecological Noveltymentioning
confidence: 99%